Penerapan Konsep Edu-Construction sebagai Upaya Peningkatan Kompetensi Aparat Desa Pagersari dalam Pengembangan Rest Area Sebagai Kawasan Wisata - Mahmud Sugandi; Mohammad Musthofa Al Ansyorie; Muhammad Aris Ichwanto; Dzul Fikri Muhammad; Kevin Reznadya Setia Budi; Mahmud Sugandi; Mohammad Musthofa Al Ansyorie; Muhammad Aris Ichwanto; Dzul Fikri Muhammad (Universitas Negeri Malang, 2023)
Abstract: The village of Pagersari, located in a highland area, possesses potential natural resources that can be developed, and its strategic location makes it suitable to become a rest area. However, the development of the rest area is still in the planning stage, with the main issue being the lack of knowledge among village officials and the local community regarding construction and cost estimation. Therefore, an